On feeding migrations of saury in the North-West Pacific Ocean - Dmitry V. Antonenko; Yury V. Novikov (Известия ТИНРО, 2017)
General patterns of the pacific saury feeding migrations in the North-West Pacific are determined on results of fishing operations conducted by a group of Russian fishery vessels in June-November, 2014. The main route of migration in June-July was directed westward and northwestward, to the open ocean. In the late summer and early autumn the saury migrated southwestward along the Oyashio Front. Towards the end of the feeding period, the main portion of large-sized saury moved along the 1st branch of Oyashio to the EEZ of Japan and its other portion moved along the 2nd branch of Oyashio to the open ocean waters. Intensity of the southwestward migrations varies from year to year in wide range in dependence on oceanographic conditions.